Make it mean! Using a ‘community of inquiry’ to improve language skills in the ESL classroom - Preece, Abdul Shakour Duncan (IIUM Press, 2013)
The purpose of the study was to explore ways of making ESL classes more engaging for language learners at the International Islamic University Malaysia (IIUM). To this end, an instructional method known as ‘Community of Inquiry' (CI) where students sit in a circle and explain, challenge and justify one another’s opinions, arguments and assertions was combined with specially written ‘thinking stories' containing philosophical issues and elements of relevance to learners' culture. Two such stories were written and taught to a class of intermediate level, ESL learners at IIUM, over a five-week period, using CI method. Qualitative research methodology was utilized to evaluate learners' responses to the method and materials. Data collection instruments included: in-depth interviews, student-diaries, focused-group observation and teacher’s diary entries. The data was subsequently transcribed, analysed and arranged into themes and sub-themes using Nvivo - a qualitative research software. The results of the research showed that CI method, combined with thinking stories, holds great potential for improving all four language skills (listening, speaking, reading and writing) in a holistic way. For example, speaking and listening were practiced through CI discussions; grammar and vocabulary were learnt in-context using the thinking stories; pronunciation was practiced during read-aloud sessions of the stories and the philosophical issues and questions discussed provided an excellent stimulus for written work. In addition, students' confidence to speak-up in class grew, as did their ability to use critical thinking skills. It appears that combining CI method with thinking stories satisfied learners' cognitive, affective and cultural needs, and this, in turn, helped to increase their intrinsic motivation to study English - an important factor for effective language learning. The paper ends by suggesting ways to improve CI method for future implementations of this new approach to second language learning.